2014
DOI: 10.1186/1471-2393-14-96
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of income-related disparities in adverse perinatal outcomes

Abstract: BackgroundTo assess and compare multiple measurements of socioeconomic position (SEP) in order to determine the relationship with adverse perinatal outcomes across various contexts.MethodsA birth registry, the Nova Scotia Atlee Perinatal Database, was confidentially linked to income tax and related information for the year in which delivery occurred. Multiple logistic regression was used to examine odds ratios between multiple indicators of SEP and multiple adverse perinatal outcomes in 117734 singleton births… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 28 publications
2
58
2
Order By: Relevance
“…Little information about those factors was available for the participants in our analysis. Shankardassk et al [37] demonstrated that adverse perinatal outcomes are related to lower socioeconomic position, and the fact that the economics of a society affect pregnancy outcomes is widespread [38]. In addition, parental education and income influence pregnancy outcomes [39].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Little information about those factors was available for the participants in our analysis. Shankardassk et al [37] demonstrated that adverse perinatal outcomes are related to lower socioeconomic position, and the fact that the economics of a society affect pregnancy outcomes is widespread [38]. In addition, parental education and income influence pregnancy outcomes [39].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, parental education and income influence pregnancy outcomes [39]. Household income is weakly related to the risk of preterm birth [37]. Other factors, such as weight gain during pregnancy, affect pregnancy complications, and Sciffres et al [40] reported that excess maternal weight leads to a higher incidence of LGA in obese and overweight women with diabetes compared to normal-weight pregnant women with diabetes.…”
Section: Discussionmentioning
confidence: 97%
“…In the USA, Black women are thought to have higher prevalence of stress than either Hispanic or White women; thus, stress has a larger influence on birth outcomes for Black women than women of the other groups [42, 53, 54]. In addition to racism and discrimination, the types of stressors that may impact birth outcomes include food insecurity, socioeconomic position, lack of access to quality education, and unsafe environment; like racism and discrimination, these factors may vary in their effects on birth outcomes for women of different racial/ethnic groups [43, 55]. …”
Section: Discussionmentioning
confidence: 99%
“…Significant stress-related risk factors which have been reviewed systematically and found to affect pregnancy and developmental outcomes include: racial disparities and discrimination [1, 2], poverty [3], and psychological distress such as depression or anxiety [4]. Moreover, relaxation techniques during pregnancy have been found to improve pregnancy outcomes [5].…”
Section: Introductionmentioning
confidence: 99%